2019
DOI: 10.3126/jist.v24i2.27259
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator Insects and their Impact on Crop Yield of Mustard in Kusma, Parbat, Nepal

Abstract: The diversity of insect pollinators and their impact on crop yield of mustard were studied in Kusma, Parbat, Nepal from December 2018 to April 2019 in four blocks with each having 12 m2 areas. Two plots; treatment and control, were established in each block. Insect diversity was observed from 8 to 16 hrs, with the interval of an hour for three consecutive months (Jan-Feb). Eighty mustard plants were randomly selected, 40 from each plot just before flowering to find the impact of insect pollination on crop yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(23 reference statements)
3
3
0
Order By: Relevance
“…Shannon-Wiener Diversity Index (H'), Evenness (E), and Margalef's Richness Index (d) were computed, which revealed the following: Shannon index (H) for species diversity 3.82, Margalef's index uals (a. Invertebrates and b. Vertebrates) of different orders (d) for species richness 9.32 and evenness index (E) 0.93. The diversity indices obtained in the current study are consistent with values reported in various agroecosystems (Deeksha et al, 2022;Usha and John, 2015;Subedi and Subedi, 2019). In this study, around 60 common pollinator visiting plants were observed in three group viz., herb, shrub, and tree (Table 2).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Shannon-Wiener Diversity Index (H'), Evenness (E), and Margalef's Richness Index (d) were computed, which revealed the following: Shannon index (H) for species diversity 3.82, Margalef's index uals (a. Invertebrates and b. Vertebrates) of different orders (d) for species richness 9.32 and evenness index (E) 0.93. The diversity indices obtained in the current study are consistent with values reported in various agroecosystems (Deeksha et al, 2022;Usha and John, 2015;Subedi and Subedi, 2019). In this study, around 60 common pollinator visiting plants were observed in three group viz., herb, shrub, and tree (Table 2).…”
Section: Resultssupporting
confidence: 91%
“…reported 43 pollinators in three orders (Hymenoptera, Diptera, and Lepidoptera) from agricultural land in Sumatera. According to earlier studies(Kearns et al, 1998;Mitra et al, 2008;Subedi and Subedi, 2019), Coleoptera, Hemiptera, Thysanoptera, Diptera, Lepidoptera, and Neuroptera constituted the vast majority pollinators. Chowdhury(contd.…”
mentioning
confidence: 99%
“…Maintenance of high germinability and vigour of seeds during storage was the result of production of well developed, bold and matured seeds owing to efficient supplementary insect pollination in this crop. The present finding agrees with the results of similar studies by earlier workers in mustard (Mahadik et al, 2019;Subedi and Subedi, 2019;Sekhon et al, 2020;Yadav et al, 2021), rape seed (Bartomeus et al, 2014;Garratt et al, 2018), canola (Shakeel and Inayatullah, 2013) and sunflower (Bhatt et al, 1996)…”
Section: Discussionsupporting
confidence: 93%
“…Foraging activities of coleopterans and hemipterans remained relatively constant throughout the day. Insect pollinators are of prime significance in pollination of different agricultural, medicinal herbal and horticultural crops mainly belong to insect orders: Hymenoptera, Lepidoptera, Coleoptera, Diptera, Thysanoptera, Hemiptera and Neuroptera (Sihag, 1988;Free, 1993;Mitra et al, 2008;Bhowmik et al, 2014;Subedi and Subedi, 2019;Singh and Mall, 2020). Thus, the present study concludes from 2007 individuals that these belong to 148 species, 47 families and 9 orders.…”
Section: Resultsmentioning
confidence: 53%
“…In addition, the effects of farming practices for better yield causes phytotoxicity and decline of favourable organisms such as predators, parasitoids, microorganisms and pollinators, particularly indiscriminate use of fertilizers and chemical insecticides (Luckman and Metcalf, 1978;Tilman et al, 2006). The insect fauna associated with agroecosystems include pests, predators, parasitoids, pollinators and non-economic importance species (Mitra et al, 2014;Mokam et al, 2014;Atencio et al, 2018;Ghani et al, 2019;Subedi and Subedi, 2019).…”
mentioning
confidence: 99%